SIN'09 - Proceedings of the Second International Conference on Security of Information and Networks: Preface - Chefranov, Alexander G.; Pieprzyk, Josef P.; Bryukhomitsky, Yury A.; Ors, Siddika Berna (My University, 2009)
[Abstract Not Available]
2nd International Conference on Security of Information and Networks, SIN'09 --